EU trade and climate policy linkages: Potentials in times of repositioning - Susanne Dröge; Felix Schenuit (Stiftung Wissenschaft und Politik (SWP), 2018)
The European Union (EU) was instrumental in successfully negotiating the Paris Agreement in 2015 and is now seeking a rapid international implementation. To this end, climate policy should be brought into line with as many foreign policies as possible, including trade policy. Free trade in environmental goods or the application of national emission standards to traded goods can accelerate climate protection globally. The legal support for this agenda through the World Trade Organization (WTO) and its dispute settlement bodies will merely be a longer-term option. Therefore, the EU and its member states should engage on two fronts in particular. Firstly, the fora of the United Nations (UN) and the WTO should make the links between the two policy areas even more transparent. Secondly, the EU can operationalise its regional free trade agreements as a lever to push for the implementation of climate policies in its partner countries. In particular, the EU should review existing trade agreements for their 'climate friendliness'. If the EU succeeds in redesigning its external relations at this interface, it can both enhance its climate policy performance and become more proactive in trade policy.
Keywords: 320